Saudi Arabia : 2018 Article IV Consultation-Press Release and Staff Report. (IMF Staff Country Reports; Country Report ;, 2018)
Reform momentum remains strong under Vision 2030. New reform initiatives are being rolled-out under the Vision Realization Programs (VRPs). Oil prices have risen over the past year and are positively affecting fiscal and external balances. Higher oil prices provide both an opportunity and a risk to the fiscal reforms.